Nationalism in the modern era: is the youth pledge still relevant? - zahra, assyfa nuri (Maliki Interdisciplinary Journal, 2025)
A B S T R A C T Globalization, which increasingly leads to Western culture, has changed the lifestyle and spirit of nationalism of the Indonesian people, especially generation Z who grew up in the digital era. In this context, the Youth Pledge pledged on 28 October 1928 faces the challenge of relevance in the midst of modernization, foreign culture, and technological development. This research analyzes how nationalism can be maintained without hampering global progress and to what extent the values of the Youth Pledge still play a role in shaping the national identity of the younger generation. Using qualitative methods through literature studies and interviews, it was found that although expressions of nationalism are changing, the spirit of unity remains important for the integrity of Indonesia. With strategies to balance global progress and Indonesian cultural values through nationalism education relevant to Generation Z, utilization of digital media, and policies that strengthen national identity, the Youth Pledge remains an inspiration for today's generation in facing the challenges of the time